Concepções de morte e estratégias de enfrentamento: um estudo com crianças de 06 a 10 anos com e sem experiência de perda por morte recente - Martins, Thaísa Barros Quintão (2006)
Studies privileging the children as spokespersons of its perceptions and experiences have shown that they are enough competent to express and they are not oblivious to the surrounding events, as in the case of the death. In this direction, this research tried to analyze the conceptions of death and coping strategies of 45 children from 6 to 10 years old and from middle social class, being 23 children with experience of recent death of affectively close people and 22 without the related experience. As method, was used the narrative interview subsidized for two scripts of halfstructuralized interview and two requested drawings to each child. The data gotten in the interviews was submitted to the content analysis and in the drawings analysis the same criteria of Fávero and Salim (1995) was used. The results exactly indicated that the children at 6 and 7 years old knew how to deal with the subject of the death, crediting more realistic than magical causes to it. The most pointed coping strategy was the solitary emotional expression of weighing followed by distraction. As for the social support, differences decurrent of experience and differences of gender were found. The children with experience of recent death had privileged only the pairs as support agents, while the others, without experience, pointed the pairs and the parents. Most of the boys and girls suggested as support, respectively, physical activities and talks. For the most part of the children drawings with experience of recent death the deceased people presented happy face expression. Differently from the children without experience of recent death, great part of the drawings of the children with experience of recent death was not colored. This research demonstrated coherence between the histories and the drawings, through the elements that repeat and complement themselves. In general way, the results had confirmed the importance of the dialogue about the death with the children, under the perspective of a healthful mourning.